Criação e desenvolvimento de spin-offs no contexto da perspectiva emergente do empreendedorismo acadêmico - Cunha, Robson Moreira (2018)
Current researches in academic entrepreneurship point out that a model exclusively focused on the exploitation of intellectual property at universities is not entirely effective and that there is an increasing scope of ways to commercialise academic knowledge. Therefore, this thesis aims to analyse how the emerging perspective of academic entrepreneurship presents itself at the federal universities in Brazil as regards the creation and development of companies that exploit academic knowledge, known as academic spin-offs. A new typology was proposed for the classification of spin-offs based on a revision of the literature, which also includes enterprises that underwent an informal transfer of technology and/or knowledge. Field research was carried out both at UFRJ and UFF. The results were obtained from the analysis of eleven spin-off cases along with the follow-up of entrepreneurship education initiatives and interviews with members of the academic community whose expertise centers on entrepreneurship. Those results show that there is a gap in the existing ways to support academic enterprises and also hint at further researches.